(untitled) (Studia theodisca, 2014)
A discussion of the long-term “Hölderlinism” of Italian poets, starting from Vigolo’s essay on Hölderlin and the music (1966), moving back to Carducci’s translations, with a critical edition of his version of Hölderlin’s Achill (1874, see the leaf reproduced in the appendix), and concluding with a look at later Italian poets up to Pusterla (2004).